2001
DOI: 10.1016/s0092-8674(01)00419-6
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Drosophila bicoid mRNA Localization Reveals a Novel Microtubule-Dependent Axis Specification Pathway

Abstract: Drosophila bicoid mRNA is synthesized in the nurse cells and transported to the oocyte where microtubules and Exuperantia protein mediate localization to the anterior pole. Fluorescent bicoid mRNA injected into the oocyte displays nonpolar microtubule-dependent transport to the closest cortical surface, and the oocyte microtubule cytoskeleton lacks clear axial asymmetry. Nonetheless, bicoid mRNA injected into the nurse cell cytoplasm, withdrawn, and injected into a second oocyte shows microtubule-dependent tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
168
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 39 publications
17
168
0
3
Order By: Relevance
“…Oocytes contain many different populations of microtubules that reorganize and change throughout different developmental stages. The microtubule network is initially polarized during early stages, with the majority of plus-ends at the posterior pole and minus-ends at the anterior pole (55,56), but later becomes less organized, with minus-ends associating with the cortex (31,(57)(58)(59)(60)(61). Microtubules are also concentrated at the posterior pole during early stages, and these microtubules reorganize and relocate to the anterior pole during stages 8-10A, forming a gradient of microtubules from anterior to posterior.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes contain many different populations of microtubules that reorganize and change throughout different developmental stages. The microtubule network is initially polarized during early stages, with the majority of plus-ends at the posterior pole and minus-ends at the anterior pole (55,56), but later becomes less organized, with minus-ends associating with the cortex (31,(57)(58)(59)(60)(61). Microtubules are also concentrated at the posterior pole during early stages, and these microtubules reorganize and relocate to the anterior pole during stages 8-10A, forming a gradient of microtubules from anterior to posterior.…”
Section: Discussionmentioning
confidence: 99%
“…2; see below). The posterior MTOC is disassembled in stages 6 -7, and several studies suggest that thereafter MTs emanate from the entire oocyte cortex (Cha et al, 2001(Cha et al, , 2002. These cortical MTs initially point toward the center of the oocyte, but in stage 8 and 9 oocytes, cortical MTs are cleared specifically from the posterior pole, allowing for the refocusing of MT plus-ends at or near the posterior ( Fig.…”
Section: After Stage 6 the Oocyte Mts Reorganize To Form The Mt Arramentioning
confidence: 99%
“…4G). More recent studies suggest that MTs emanate from the lateral cortices as well (Cha et al, 2001(Cha et al, , 2002. Staining with antibodies for MTOC components has yielded conflicting results.…”
Section: The Mechanism Governing Mt Organization In the Midoogenesis mentioning
confidence: 99%
“…Several different model systems have been used for dissecting RNA transport. In Drosophila oocytes, microtubules show gross polarity with the plus-end at the posterior and the minus-end at the anterior of the oocytes (7,8). It has been shown that localization of oskar mRNA to the posterior pole is mediated by kinesin-1 (9, 10), whereas anteriordorsal localization of gurken mRNA and anterior localization of bicoid mRNA is mediated by dynein (8,11).…”
mentioning
confidence: 99%